Stability of 11-nor-Δ9-carboxy-tetrahydrocannabinol glucuronide in plasma and urine assessed by liquid chromatography-tandem mass spectrometry - Skopp, Gisela; Pötsch-Schneider, Lucia Edeltraud (Clinical chemistry, 2002)
Unconjugated 11-nor-Δ9-carboxy-tetrahydrocannabinol (THCCOOH) in blood and urine has been proposed as a valuable marker, but the glucuronide (THCCOOglu) is present in considerably higher concentrations than the parent drug. Acyl glucuronides have been shown to be potentially reactive conjugates, which may affect the in vitro metabolite pattern.